Vibrational threshold equal to the barrier height for an endothermic reaction: Li+FH→LiF+H on an ab initio potential-energy surface - Ibrahim Ali , Noorbatcha; N., Sathyamurthy (American Institute of Physics (AIP), 1981)
Vibrational threshold equal to the barrier height for an endothermic reaction: Li+FH→LiF+H on an a b i n i t i opotential energy surface is considered.